Evaluation of biofilm of Vibrio anguillarum for oral vaccination of Asian seabass, Lates calcarifer (BLOCH, 1790). Issue 94 (November 2019) - Ram, Mohit Kumar; Naveen Kumar, B.T.; Poojary, Sathish Rama; Abhiman, P.B.; Patil, Prakash; Ramesh, K.S.; Shankar, K.M.
Abstract: The present study evaluated the biofilm (BF) of Vibrio anguillarum for oral vaccination of Asian seabass, Lates calcarifer . An 80-day experiment was carried out in circular fiber-reinforced plastic (FRP) tanks using free cell (FC) and BF of Vibrio anguillarum with triplicate in each. Heat-inactivated FC and BF cells at 10 7, 10 10 and 10 13 CFU/g fish/d were fed to fish for 20 days, agglutination antibody titer estimated at each 10 days interval up to 60-day post vaccination. As compared to FC and control there was a significant increase in agglutinating antibody titer in the biofilm vaccinated fishes. Among the 3 doses, BF at 10 10 cfu/g fish/d was considered the ideal dose for vaccination. Relative percentage survival (RPS) was higher in biofilm vaccinated fish (85.4%) compared to that with free cells (27.0%). The study demonstrated the better performance of V. anguillarum biofilm oral vaccine compared that with free cell vaccine in L. calcarifer . The study further supports better performance of biofilm vaccine model with one more bacterial pathogen in a high carnivore fish. Highlights: Vaccinated feed prepared by incorporating heat -inactivated Vibrio anguillarum biofilm (BF) and free cell (FC) vaccines. Asian seabass were orally vaccinated with heat-inactivated FC and BF cells at 10 7, 10 10 and 10 13 CFU/g fish/d for 20 days. Agglutinating antibody titer was significantly increased in the biofilm vaccinated fishes. LD50 dose of Vibrio anguillarum detremined to be 10 6 CFU/ g fish. BF vaccinated groups at 10 10 cfu/g fish/d showed the highest relative percentage survival (RPS) compare to control and FC.